The global politics of AIDS - Harris, Paul G.; Siplon, Patricia D. (Lynne Rienner, 2007)
With more than 40 million people living with HIV/AIDS, and more than 25 million dead from related diseases since the early 1980s, the need to understand the causes and impact of the pandemic is manifest. In response, The Global Politics of AIDS explores power and politics at multiple levels, ranging from individual behavior to corporate boardrooms to international institutions and forces. The authors combine careful scholarship with sensitivity to both the suffering of those afflicted and the frustration of those seeking to bring about meaningful change. All royalties from sales of the book will be donated to AIDS-related organizations